2020
DOI: 10.1049/iet-ipr.2020.0688
|View full text |Cite
|
Sign up to set email alerts
|

Cervical cancer detection in cervical smear images using deep pyramid inference with refinement and spatial‐aware booster

Abstract: With the development of artificial intelligence and image processing technology, more and more intelligent diagnosis technologies are used in cervical cancer screening. Among them, the detection of cervical lesions by thin liquid‐based cytology is the most common method for cervical cancer screening. At present, most cervical cancer detection algorithms use the object detection technology of natural images, and often only minor modifications are made while ignoring the specificity of the complex application sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 57 publications
0
12
0
Order By: Relevance
“…The most important findings of our study are as follows: (1). There are currently few network architectures designed specifically for cervical cancer cell detection in Pap smear images [42,[44][45][46]. Based on one of the currently top-performing detectors faster RCCN-FPN [57]…”
Section: The Main Findings Of the Studymentioning
confidence: 99%
See 2 more Smart Citations
“…The most important findings of our study are as follows: (1). There are currently few network architectures designed specifically for cervical cancer cell detection in Pap smear images [42,[44][45][46]. Based on one of the currently top-performing detectors faster RCCN-FPN [57]…”
Section: The Main Findings Of the Studymentioning
confidence: 99%
“…The cells have been manually classified into five cell types without pre-neoplastic alteration by expert cytopathologists. Some previous studies have relied on image collections of cut-out images [41,43] of clean images or positive samples [42]. Despite of the seemingly good performance, these results are not so realistic and clinically relevant.…”
Section: Limited Train Dataset and Unlabeled Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…The object detection methods have also begun to find applications for cervical cancer detection in cervical cytology images. At present, there are few network architectures designed specifically for the specific task of cervical cancer detection [ 41 , 42 , 43 , 44 , 45 , 46 ]. Xu et al [ 45 ] used the generic Faster RCNN for the detection of abnormal cells in cervical smear images scanned at 20× and showed that detection of various abnormal cells was feasible.…”
Section: Introductionmentioning
confidence: 99%
“…Tan et al [ 44 ] also used Faster RCNN architecture for cervical cancer cell detection in ThinPrep cytologic test (TCT) images scanned with a seamless slider at up to 400× and achieved AUC of 0.67. More recently, Ma et al [ 42 ] proposed an improved Faster RCNN-FPN architecture for cervical cancer detection in cropped patches out of positive Pap smear images. They designed a lightweight booster consisting of a refinement and spatial-aware module, aimed to enhance feature details and spatial context information.…”
Section: Introductionmentioning
confidence: 99%